Desenvolvimento de artefato tecnológico para controle de estoque de reagentes em um laboratório de bromatologia. - Silva Neto, Vicente (Universidade Federal de São Carlos, 2025)
Federal universities face significant challenges related to the shortage of human and financial resources, compounded by the continuous consumption of supplies used in teaching, research, and extension activities. In this context, it is essential to adopt inventory control systems that ensure the efficient use of resources and the continuity of academic activities. In university laboratories, chemical reagents are stored in small stockrooms and, in many cases, are subject to supervision by the Federal Police, which requires specific licenses, strict usage control, and the presentation of storage conditions during inspections. The lack of structured control systems and the unrestricted access of students to these environments contribute to disorganization, material losses, and increased risk of accidents. In view of this scenario, this study aims to develop and implement an automated system for controlling chemical reagent inventories in order to ensure greater accuracy, traceability, and safety in the management of laboratory supplies. The research adopts the Design Science Research (DSR) method, which proposes the development of technological solutions applied to practical problems. The implemented system is based on RFID (Radio Frequency Identification) technology integrated with an electronic weighing scale, allowing the identification of each reagent individually and the real-time monitoring of its consumption. The results indicate that the integration of these technologies enables a hybrid inventory control model that combines continuous and periodic review, associated with the FIFO (First In, First Out) criterion and the physical reorganization of the laboratory. This approach increases record accuracy, reduces human errors, and improves operational efficiency. Furthermore, the developed system, based on open-source software and low-cost components, demonstrates reliability, ease of use, and automatic report generation, eliminating the need for extensive training. It is concluded that the proposed solution is economically viable, replicable, and capable of significantly contributing to the safety, organization, and sustainability of chemical reagent management in academic laboratories.
Development of a technological artifact for reagent inventory control in a bromatology laboratory
Keywords: Controle de estoque; Reagentes Químicos; Design Science Research (DSR); RFID (Identificação por Radiofrequência); ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO; 9. Indústria, Inovação e Infraestrutura